1998
DOI: 10.1021/bi971944c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functioning of Dihydro- and Tetrahydropterins in Supporting Electron Transfer, Catalysis, and Subunit Dimerization in Inducible Nitric Oxide Synthase

Abstract: The nitric oxide synthases (NOS) are the only heme-containing enzymes that require tetrahydrobiopterin (BH4) as a cofactor. Previous studies indicate that only the fully reduced (i.e., tetrahydro) form of BH4 can support NO synthesis. Here, we characterize pterin-free inducible NOS (iNOS) and iNOS reconstituted with eight different tetrahydro- or dihydropterins to elucidate how changes in pterin side-chain structure and ring oxidation state regulate iNOS. Seven different enzyme properties that are important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
161
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(182 citation statements)
references
References 62 publications
19
161
2
Order By: Relevance
“…These findings reveal that the stabilizing effects of H % Bip are probably independent of the composition of the C-6 pterin side chain. Similar conclusions were made by Presta et al [54] for NOS-II on dimer reassembly by various analogues of pterin after urea-induced monomerization. In the present study, PHS-32 was less effective than H % Bip at stabilizing dimeric NOS-I and this might be related to the inability of PHS-32 to support enzyme catalysis and allosterically regulate -arginine binding.…”
Section: Reagent and Nos-bound H 4 Bip : Reaction With O 2 − Dsupporting
confidence: 87%
“…These findings reveal that the stabilizing effects of H % Bip are probably independent of the composition of the C-6 pterin side chain. Similar conclusions were made by Presta et al [54] for NOS-II on dimer reassembly by various analogues of pterin after urea-induced monomerization. In the present study, PHS-32 was less effective than H % Bip at stabilizing dimeric NOS-I and this might be related to the inability of PHS-32 to support enzyme catalysis and allosterically regulate -arginine binding.…”
Section: Reagent and Nos-bound H 4 Bip : Reaction With O 2 − Dsupporting
confidence: 87%
“…Purified NOS-I exists as a stable homodimer (27), and monomerization was only described to occur under denaturing conditions, i.e. in the presence of 4% SDS (16) or 5 M urea (12). However, we observed monomerization to occur also during L-arginine turnover, i.e.…”
Section: Discussionmentioning
confidence: 61%
“…For example, H 4 Bip acts catalytically as the sole oxygen acceptor for the aromatic amino acid hydroxylases (1); for NOS, this role is already fulfilled by the cytochrome P 450 -type heme (10,11). In a recent study (12) it was shown that heme iron reduction can take place independently of the pterin ring oxidation state. Although this would indicate a requirement for fully reduced pterin at a reaction step beyond heme iron reduction, recent evidence (13) suggests that the reduction of the oxyferroheme complex may be the main function of H 4 Bip in NOS catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BH 4 is essential for the production of nitric oxide, an endothelial vasorelaxing factor, by NOS and may hence serve as a biomarker of endothelial dysfunction. While BH 2 may bind to NOS just like BH 4 (Vásquez-Vivar et al, 2002;Crabtree et al, 2008), it does not support the formation of nitric oxide (Presta et al, 1998) and instead superoxide is formed (Vásquez-Vivar et al, 2002). Studies have suggested that the ratio of BH 4 to BH 2 correlates better with endothelial function than the absolute concentration of BH 4 (Noguchi et al, 2011;Crabtree et al, 2008;Takeda et al, 2009;Kar & Kavdia, 2011).…”
Section: Introductionmentioning
confidence: 99%